2015
DOI: 10.1111/jzo.12233
|View full text |Cite
|
Sign up to set email alerts
|

Blind toads in paradise: the cascading effect of vision loss on a tropical archipelago

Abstract: On the archipelago of Fernando de Noronha, nearly half of the individuals in the invasive population of Cururu toads have mouthpart, limb or eye deformities. Among these, a subset of adult toads is completely blind or has just one functional eye. In this study, we examined the consequences of this vision loss in relation to feeding and reproductive biology. Blind toads were handicapped relative to normal toads, whereas the half-blind individuals were intermediate. In contrast to the expected active hunting mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Similar eye deformities in toads have also been reported in at least two other island systems: firstly on the R. marina population in Bermuda (Bacon et al, 2006), and later on a Cururu toad (Rhinella jimi) population introduced to the island of Fernando de Noronha (Brazil) (Toledo & Ribeiro, 2009;Tolledo & Toledo, 2015). Although toads show high rates of malformations in both cases, the causes have yet to be confirmed.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Similar eye deformities in toads have also been reported in at least two other island systems: firstly on the R. marina population in Bermuda (Bacon et al, 2006), and later on a Cururu toad (Rhinella jimi) population introduced to the island of Fernando de Noronha (Brazil) (Toledo & Ribeiro, 2009;Tolledo & Toledo, 2015). Although toads show high rates of malformations in both cases, the causes have yet to be confirmed.…”
supporting
confidence: 62%
“…Ocular abnormalities (e.g. Boon-Hee et al, 2013;Fernández-Loras et al, 2016;Tolledo & Toledo, 2015) are amongst the least frequently reported cases (Reeves et al, 2013;Laurentino et al, 2015), and can be the result of many factors such as environmental contaminants (metals and petroleum hydrocarbons) (Bacon et al, 2013), pesticides (Gurushankara et al, 2007), emerging diseases (Burton et al, 2008) and predation (Lannoo, 2008).…”
mentioning
confidence: 99%
“…g ., chemical pollutants) or intrinsic handicaps such as inbreeding depression (see [ 78 , 79 ]). Rhinella jimi has been established in Fernando de Noronha for about 100 years and these toads are thriving despite showing high prevalence of multiple types of abnormalities [ 78 , 133 ]. This is another example of how invasive species can benefit from the lack of local competitors and predators in oceanic islands [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors considered that inbreeding would lead to the same types of anomalies in all affected individuals, not to the heterogeneous observed. However, the high frequency of malformations detected in insular populations of toads from Brazil, ranging from mouthpart anomalies, limb reduction to loss of eyes, has been associated with genetic structure and inbreeding (Toledo and Ribeiro 2009, Tolledo and Toledo 2015, Bessa-Silva et al 2016, Reboucas et al 2019. The small population of Zapata's Toad is restricted to a few localities from the eastern part of the Zapata region, Matanzas province to the east of Cienfuegos City, Cienfuegos Province, associated with coastal microphyllous evergreen forest with different level of human perturbation.…”
Section: A B C D E F G Hmentioning
confidence: 99%